Full-scale flying shape measurement of offwind yacht sails with photogrammetry. (15th November 2016) - Deparday, Julien; Bot, Patrick; Hauville, Frederic; Augier, Benoit; Rabaud, Marc
Abstract: Yacht downwind sails are complex to study due to their non-developable shape with high camber and massively detached flow around thin and flexible membranes. Numerical simulations can now simulate this strong Fluid-Structure Interaction, but need experimental validation. It remains complex to measure spinnaker flying shapes partly because of their inherent instability, like luff flapping. This work presents full-scale experimental investigation of spinnaker shapes with simultaneous measurement of aerodynamic loads on the three sail corners, with navigation and wind data. The experimental set-up and photogrammetric method are presented. Results are analysed in the whole range of apparent wind angle for this sail. The spinnaker shape shows dramatic variations and high discrepancies with the design shape. The photogrammetric measurement produces the full 3D flying shape with a satisfactory accuracy. Even if only steady state results are given here, this new system enables time-resolved measurement of flying shapes and thus flapping of spinnakers to be investigated, which is valuable for yacht performance optimisation. On top of sailing yacht applications, the method is useful in any application where a non-developable 3D shape is to be determined, and particularly when it results from the Fluid Structure Interaction of a flexible structure with a complex flow. Abstract : Graphical abstract: Abstract : Highlights: A new method to measure the 3D shape of a flexible membrane inflated by the wind. Good accuracy is found for yacht testing in real sailing conditions. Yacht offwind sail shapes and aerodynamic forces are given for various wind angles. A new representation of the non-developable shape is proposed. The method is suitable for dynamic analysis of unsteady Fluid Structure Interaction.